2008
DOI: 10.1177/112972980800900204
|View full text |Cite
|
Sign up to set email alerts
|

Vena Cava Filters: A Synopsis of Complications and Related Topics

Abstract: Deep venous thrombosis and pulmonary embolism constitute common preventable causes of morbidity and mortality. The incidence of venous thromboembolism (VTE) continues to increase. Standard anticoagulation therapy may reduce the risk of fatal PE by 75% and that of recurrent VTE by over 90%. For patients who are not candidates for anticoagulation, a vena cava filter (VCF) may be beneficial. Despite a good overall safety record, significant complications related to VCF are occasionally seen. This review discusses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…4 However, 20% of the complications reported in the MAUDE database were perforations; in addition, Stawicki et al reported the rate of clinically significant penetration to be 0.4%. 52 .…”
Section: Filter Complicationsmentioning
confidence: 99%
“…4 However, 20% of the complications reported in the MAUDE database were perforations; in addition, Stawicki et al reported the rate of clinically significant penetration to be 0.4%. 52 .…”
Section: Filter Complicationsmentioning
confidence: 99%
“…Specific indications, limitations, complications, and costs should be well known to providers. One last area not specifically included in this review, but certainly deserving a brief mention, is the use of bedside ultrasound in detection, follow-up, and treatment of a variety of peripheral arterial and venous conditions [112][113][114][115][116][117][118], including deep vein thrombosis [119,120].…”
Section: Ultrasound In Hemodynamic Monitoring and Volume Status Estimmentioning
confidence: 99%
“…96 However, according to the MAUDE database, IVC filter perforations account for up to 20% of reported complications, with clinically significant perforation occurring 0.4% of the time. 102 Studies have reported higher complication rates with retrievable filters compared with permanent ones, with one study attributing 87% of filter complications to retrievable filters. 103 IVC filters are commonly assessed with contrastenhanced CT or CT venograms to evaluate filter integrity, tilt, and caval penetration.…”
Section: Venous Angioplastymentioning
confidence: 99%